Analisis perilaku impulse buying dalam e-commerce perspektif bisnis syariah - Dewinta Dora Sarrascalao (Journal of Business & Banking, 2018)
Supported by the development of technology and information, some people change their buying behavior patterns from those initially offline to online systems. This study aims to examine the impulse buying behavior of online consumers in e-commerce which is viewed from the perspective of sharia business. The approach os this study is a qualititative method with a type of case study. The method of data collection in this study was to use interview methods, observation and documentation to informants. The unit of analysis of this study were nine consumers who made purchase online through a marketplace consisting of six buyers in Lazada, two buyers in  Zalora, and one buyer in BliBli, in addition there was one seller at Lazada. The results of the study show that 1)Consumers or individuals who have inclusive behavior in Lazada, Zalora and BliBli are included in the type of suggestion impulse behavior and planned impulse buying types (purchases depend on sales conditions). 2)Impulse buying behavior in e-commerce has fullfilled one or more sharia business principles, namely Lazada fulfills the principles of tauhid, adliyah, hurriyah, musawwah, and taawun, the Zalora fulfills the nabawi prinsiple, adliyah, musawwah, and hurriyah the BliBli fulfills the nabawi prinsiples, adliyah,  hurriyah, musawwah and ta’awun.